TRANSFER TEKNOLOGI TREAT METHODS SEBAGAI TINDAKAN PENGENDALIAN HAMA DAN PENYAKIT CABAI DI KWT ANYELIR DESA HAJIMENA LAMPUNG SELATAN - Putri, Sekar Utami; Safitri, Betari; Febria, Dila; Darma, Wika Anrya; Khafidan, Abied (Universitas Mataram, 2026)
The Anyelir Women's Farmers Group (KWT) is a women's farmer group active in vegetable cultivation in Hajimena Village, Natar District. This area is classified as lowland and has ultisol soil. This is a challenge for the KWT in cultivating in the existing geographical conditions. Ultisol soil is classified as soil with a low pH, cation exchange capacity (CEC), and low organic matter content, resulting in inefficient fertilizer application. This affects the optimization of vegetable commodity production, especially chilies. Other problems with chilies besides ultisol soil are whitefly attacks and curly leaf disease. This requires integrated and sustainable control of plant pests. The Treat Method is a combination of technical and biological cultural control in chili cultivation. The purpose of this activity is to transfer technology regarding proper chili cultivation with sustainable control of plant pests for optimal results. The methods used are education, skill development, and process evaluation. The results of this activity indicate an increase in knowledge and skills among KWT members. Whitefly and curly leaf disease attacks can be suppressed by up to 2.5% and 20%, respectively.